Cardiovascular Risk Factors Among Patients With Vestibular Neuritis. (August 2017) - Oron, Yahav; Shemesh, Shay; Shushan, Sagit; Cinamon, Udi; Goldfarb, Abraham; Dabby, Ron; Ovnat Tamir, Sharon
Objective: To investigate the correlation between cardiovascular risk factors (CVRFs) and vestibular neuritis (VN) in hospitalized adult patients. Methods: A cross-sectional retrospective study was conducted in a tertiary hospital setting. The medical records of patients (aged over 18 years old) who were hospitalized between the years 2005 and 2014 with the diagnosis of VN were retrieved. Inclusion criteria were: (1) acute vertigo lasting for at least 24 hours, (2) absence of auditory complaints, (3) horizontal unidirectional nystagmus present during physical examination, and (4) absence of neurological symptoms or signs. The ratio of CVRFs among VN patients was compared to the ratio of those among the general Israeli population. Results: A significantly higher prevalence of CVRFs was found among VN hospitalized patients in comparison to the general population ( P < .05). Furthermore, a significant correlation ( P < .001) was found between the patients' age and the number of CVRFs (r = .387). A positive correlation (r = .643) was found between the number of CVRFs and VN in each age group ( P = .119). Conclusion: There may be a possible interrelation between CVRFs and VN. This correlation can be caused by occlusion of small blood vessels leading to labyrinthine ischemia and apparition of symptoms of VN.